Pistia stratiotes as Effective Larvicide against Aedes aegypti - Usman Fajar Saputra; Delima Engga Maretha; Asnilawati Asnilawati (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
World Health Organization (WHO) noted that Indonesia was the country with the highest cases of Dengue Hemorrhagic Fever in Southeast Asia. Control efforts include vector observation and monitoring, one of which is larvicides. This study aims to determine the effectiveness of Apu-apu (Pistia stratiotes) leaf extract to inhibit the growth of the third instar larvae of the Aedes aegypti. The design of this study was Completely Randomized Design (CRD). The treatment in this study was repeated 3 times using 4 treatments (negative control treatment, given extract of 10 ml, 30 ml, 50 ml). The results showed that Apu-apu leaf extract had different effects on each test concentration (10ml, 30ml and 50ml). The higher the concentration, the greater mortality of Aedes aegypti larvae. ANOVA test showed that Apu-apu leaf extract (Pistia stratiotes) had an effect with the F=94.667, p= 0,000 on larvae mortality. The ability of Apu-apu leaf extract to kill larvae in LC50 value was 4.0% per minute, analyzed using probit regression. P. stratiotes could be an effective larvicide against A. aegypti third instar larvae (p=0,000).